Anemia of Chronic Disease in Patients With Cardiovascular Disease - Lanser, Lukas; Fuchs, Dietmar; Scharnagl, Hubert; Grammer, Tanja; Kleber, Marcus E.; März, Winfried; Weiss, Günter; Kurz, Katharina (Frontiers in Cardiovascular Medicine, 2021)
Objective: Anemia is often found in patients with coronary artery disease (CAD) or acute coronary syndrome (ACS) and related to disease severity. Our study investigated the relationship between anemia, iron homeostasis and inflammation in CAD and examined their influence on the outcome of patients. Patients and methods: Markers of immune activation (neopterin, interleukin [IL]-12, IL-6, high sensitive C-reactive protein (hsCRP), fibrinogen, serum amyloid A [SAA]) and iron metabolism (ferritin, transferrin saturation, hemoglobin) were determined in 2082 patients (68.7 % men, median age 63 years) from the Ludwigshafen Risk and cardiovascular Health (LURIC) cohort. Patients were followed-up for a median of 9.81 years. Results: 960 patients (46.1 %) presented with chronic CAD, 645 patients (31.0 %) had an ACS, and 477 patients (22.9 %) presented with no CAD in coronary angiography (CAG). Anemia (n = 357, 17.1 %) was associated with disease severity (reflected by more progressed stenosis in CAG, CCS and NYHA classes, and a lower LV-EF), a higher cardio-cerebrovascular event rate and higher levels of inflammatory markers. Interestingly, anemia was only predictive for an adverse outcome in patients with elevated inflammatory markers. Accordingly, anemia of chronic disease (ACD) was associated with a higher cardio-cerebrovascular event-rate in the subsequent two years as compared to patients with other types of anemia or without anemia (14.3% vs. 6.1% vs. 4.0%, p < 0.001). Conclusions: This study confirms that anemia and immune activation are strongly related to cardiovascular disease progression and an adverse outcome. Our data suggest that the association of anemia with disease severity and outcome might mainly be due to underlying inflammation.